Mechanical characteristics of ultra-shallow buried high-speed railway tunnel in broken surrounding rock during construction - Hao, Shaoju; Fei, Ruizhen; Yu, Jia (Archives of Civil Engineering, 2022)
The mechanical state of broken surrounding rock during the construction of ultra-shallow buried high-speed railway tunnel is very complicated, seriously affecting the construction safety. Taking Huying Xishan tunnel on Beijing-Shenyang Line as engineering background, MADIS/GTS NX numerical simulation and field test methods are used to analyze the characteristics of stress field, overall displacement, horizontal convergence of tunnel sidewalls and vault settlement during construction. The main mechanical characteristics of ultra-shallow buried high-speed railway tunnel with broken surrounding rock include: (1) After the stress redistribution, the stress concentration occurs at the boundary of the tunnel sidewall and surrounding rock, and the vertical displacement of tunnel vault and bottom appears obviously. (2) The horizontal displacement on both sides of the initial lining is obvious, while the horizontal displacement on the upper and lower support is small. The maximum lateral displacement of the initial lining is 1.71 cm, while the maximum vault settlement of the lower invert is 9.3 cm. (3) Both the horizontal convergence and the vault settlement increase with time. The growth rate is large in the early stage and tends to be stable in the later stage. (4) Compared with exponential and hyperbolic functions, the logarithmic function is most suitable for regression analysis of horizontal convergence and measured vault settlement data, and its fitting accuracy is higher than 90%.
Keywords: broken surrounding rock; ultra-shallow buried; high-speed railway tunnel; numerical simulation; deformation characteristics